Impact of Constructivist Pedagogy in Developing RACE among Children - Darji, Chiragbhai Mahendrabhai (Journal of Literature Language and Academic Studies, 2023)
Language is a medium of expression and is inevitable skills to develop among every child. The New Education Policy-2020 focuses on building a bridge between skills and knowledge. Thus, the evaluation system of Language in school is like a subject. Therefore, the researcher carried out a survey on the students who have been taught through the constructivist pedagogy of teaching English. The said pedagogy is not from the bunch of pedagogical strategies suggested in English language teaching. English is taught in India through the foreign prescribed pedagogy and Indian interdisciplinary or multidisciplinary pedagogies are not prescribed and practiced. Thus, the researcher based on the research, collected the opinions of the students who have experienced learning through constructivist pedagogy. In the research, the researcher collected the data from one Gujarati medium school of Anand District, Gujarat India. The students were made to share the genuine feedback over the intervention programme. The findings of the study say that the constructivist approach is effective in developing the rapid acquisition of competence in English than the other foreign pedagogy of teaching English. The students also said that the constructivist pedagogy help in developing content, skills and attitude towards English language learning and teaching. Thus, the study presents the positive impact of inter-disciplinary pedagogy in developing race among the children of upper primary.